1989
DOI: 10.1152/ajpregu.1989.256.1.r217
|View full text |Cite
|
Sign up to set email alerts
|

Central action of acidic fibroblast growth factor in feeding regulation

Abstract: A phasic increase in activity similar to that of acidic fibroblast growth factor (aFGF) was detected in the cerebrospinal fluid of rats after feeding or after an intraperitoneal injection of glucose. This FGF-like activity in the cerebrospinal fluid was bioassayed in two systems: depression of the feeding response of Hydra and DNA synthesis-stimulating activity in BALB/c 3T3 cells after fractionation on a heparin affinity column. Dynamic feeding-related changes in activity of aFGF, basic FGF, and other growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Therefore it is likely that the difference may be derived from specific activities of haFGF and CS23. Hanai et al (1989) has reported that aFGF may participate in the regulation of feeding at the level of the central nervous system. A phasic increase of aFGF-like biological activity was detected in the cerebrospinal fluid and intracerebroventricular administration of aFGF sup- pulses at 60 Hz was significantly enhanced and LTP was generated by the injection of 40 pg/ml CS23 in both non-fasted (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it is likely that the difference may be derived from specific activities of haFGF and CS23. Hanai et al (1989) has reported that aFGF may participate in the regulation of feeding at the level of the central nervous system. A phasic increase of aFGF-like biological activity was detected in the cerebrospinal fluid and intracerebroventricular administration of aFGF sup- pulses at 60 Hz was significantly enhanced and LTP was generated by the injection of 40 pg/ml CS23 in both non-fasted (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that a phasic increase of FGFlike biological activity was detected in the cerebrospinal fluid after feeding or after intraperitoneal injection of glucose (Hanai et al, 1989). It is possible that the effects of FGF on hippocampal LTP differ with feeding condition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fasting reduces, and refeeding increases, endogenous hypothalamic FGF expression (mRNA and protein levels), and icv-administered FGF1 or -2 decreases food intake in rats (20,40). Feeding suppression by FGF1 is associated with upregulation of c-Fos activity in periventricular astrocytes (58) and increased protein kinase C activity in glucose-sensitive neurons of the lateral hypothalamus (41).…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that intracerebroventricular (icv) injection of FGF1 or -2 decreases food intake (Refs. 20,22,40, and 41 and references therein) and that polyclonal antibodies against either ligand or FGFR1 induce weight gain (28,52).…”
mentioning
confidence: 99%
“…Therefore, it is possible that there are different regulational mechanisms on the receptors which have different binding affini ties to aFGF and bFGF, and these two FGFs have different neurotrophic effects in the brain, although we have not done binding ex periments. On the other hand, it has been re ported that aFGF may be concerned with the regulation of feeding at the level of the central nervous system (30,31). Therefore, it is possi ble that bFGF might participate in the neuro trophic effect in the brain by binding to bFGF-sensitive receptors, and on the other hand, aFGF might participate in other effects such as feeding regulation and neurotrophic effect in the retina by binding to aFGF-sensi tive receptors.…”
Section: Discussionmentioning
confidence: 99%